Institutional Frameworks, Venture Capital and the Financing of European New Technology‐based Firms. (20th November 2013) - Vanacker, Tom; Heughebaert, Andy; Manigart, Sophie
Abstract Manuscript Type Empirical Research Question/Issue We first study how cross‐country differences in shareholder protection against self‐dealing and personal bankruptcy laws affect the financing of new technology‐based firms (NTBFs). Second, we study how venture capital (VC) investors – as expert monitors and initiators of "good" governance practices in firms – moderate aforementioned relationships. Research Findings/Insights Using a unique longitudinal dataset of 6, 813 NTBFs from six European countries, we find that better shareholder protection rights increase the probability of raising external equity financing and allow firms to raise larger amounts of equity financing. Less forgiving personal bankruptcy laws decrease the probability of raising debt financing and limit the amount of debt financing that is raised. VC ownership strengthens the aforementioned relationships. Theoretical/Academic Implications This study is one of the first to provide evidence on the relationship between national legal systems and the financing of private NTBFs. We further address a recurring call for more research on the interaction between country‐level legal systems and firm‐level corporate governance. In particular, we show that expert monitors, such as VC investors, strengthen the relationship between national legal systems and NTBF's access to external financing. Practitioner/Policy Implications Policy makers often focus on increasing the supply of VC financing as a panacea for external financing constraints experienced by NTBFs. This study shows that VC ownership is particularly effective at increasing firms' access to external financing in countries with strong investor protection rights and entrepreneur‐friendly personal bankruptcy laws.